Creating an Autonomous Chair Role - Christine N Dalton; Kara E Stooksbury; Jeremy J Buckner; Laura Wadlington (Academic Chairpersons Conference Proceedings, 2015)
This presentation will describe modifications to the flat organizational model on our campus and the impact of those changes on department chairs. More specifically, we will discuss how a task force of department chairs developed an approach creating a more autonomous role for the chair.
Keywords: flat administrative model; team-based approach; autonomy of chairs; chairs council; organizational structure